2019
DOI: 10.2196/10798
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Delivered Peer Physical Activity Counseling Program for Individuals With Spinal Cord Injury: Protocol for Development and Pilot Evaluation

Abstract: Background Leisure-time physical activity (LTPA) is a critical component of a healthy lifestyle for individuals with spinal cord injury (SCI). However, most individuals are not sufficiently active to accrue health benefits. The Active Living Lifestyles program for individuals with SCI who use manual wheelchairs (ALLWheel) targets important psychological factors that are associated with LTPA uptake and adherence while overcoming some barriers associated with participation restrictions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 96 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…The exploratory phase of the Medical Research Council Framework [27] was conducted in three Canadian cities (Quebec, Montreal, and Vancouver) using a single-arm pre-post design previously described by Best et al [22]. The study was approved by local research ethics boards at each site.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The exploratory phase of the Medical Research Council Framework [27] was conducted in three Canadian cities (Quebec, Montreal, and Vancouver) using a single-arm pre-post design previously described by Best et al [22]. The study was approved by local research ethics boards at each site.…”
Section: Designmentioning
confidence: 99%
“…To further address the LTPA needs of people who use wheelchairs, Best et al developed a peer-led program called active living lifestyles for wheelchairs users (ALL-Wheel) [22]. The ALLWheel program engages peers as LTPA coaches and uses smartphones to provide LTPA counseling for people with disabilities who use wheelchairs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for the lack of trials might be due to barriers of transportation and lack of face-to-face interaction with healthcare professionals [ 22 ]. Two pilot trials that integrated community-based physical activities and telephone counseling from physiotherapists indicated positive effects of an activity-based intervention on functional improvement and physical fitness for community dwellers with SCI [ 23 , 24 ]. In addition, previous research also indicated positive effects of physical activities on SCI survivors’ mood (e.g., depression) and subjective well-being [ 12 ].…”
Section: Introductionmentioning
confidence: 99%